2019
DOI: 10.1002/jbm.a.36646
|View full text |Cite
|
Sign up to set email alerts
|

Engineering molecularly mobile polyrotaxane surfaces with heparin‐binding EGF‐like growth factors for improving hepatocyte functions

Abstract: Hepatocytes in vitro may be useful for treating various types of liver diseases, but these cells immediately lose their functions. Here, we designed sulfonated‐polyrotaxane (PRX) surfaces with immobilized heparin binding‐epidermal growth factor‐like growth factors (HB‐EGFs) for improving hepatic functions. Sulfonated‐PRX triblock copolymers, composed of sulfopropyl ether‐modified α‐cyclodextrins (α‐CDs) threaded onto a poly(ethylene glycol) (PEG) chain as a PRX segment and poly(benzyl methacrylate) at both ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…To solve this problem, we have focused on hydrogels based on polyrotaxanes (PRXs) [20]. PRX is a supermolecule formed by the self-assembly of linear polymers (e.g., polyethylene glycol (PEG)) and cyclic molecules (e.g., α-cyclodextrin (α-CD), and exhibits a mechanically interlocked structure in which many cyclic molecules are threaded on the polymers ( Figure 1A) [21,22]. Ito and co-workers have reported that the use of PRX cross-linkers comprised many acrylate-modified α-CDs and PEG improve the mechanical properties of hydrogels [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To solve this problem, we have focused on hydrogels based on polyrotaxanes (PRXs) [20]. PRX is a supermolecule formed by the self-assembly of linear polymers (e.g., polyethylene glycol (PEG)) and cyclic molecules (e.g., α-cyclodextrin (α-CD), and exhibits a mechanically interlocked structure in which many cyclic molecules are threaded on the polymers ( Figure 1A) [21,22]. Ito and co-workers have reported that the use of PRX cross-linkers comprised many acrylate-modified α-CDs and PEG improve the mechanical properties of hydrogels [23].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is no literature on cellular responses on gelatin hydrogels with the mechanical hysteresis property before and after repeatedly stretching. in which many cyclic molecules are threaded on the polymers ( Figure 1A) [21,22]. Ito and co-workers have reported that the use of PRX cross-linkers comprised many acrylate-modified α-CDs and PEG improve the mechanical properties of hydrogels [23].…”
Section: Introductionmentioning
confidence: 99%
“…Growth factors facilitate the proliferation and differentiation of progenitor and stem cells, as well as directly induce growth of differentiated cells such as hepatocytes in the liver or osteoblasts in bone (Uebersax et al., 2009 ). They also have an important regulatory role in human immunity, hematopoietic regulation, tumorigenesis, inflammatory infection, wound healing, angiogenesis, cell differentiation, cell apoptosis, morphogenesis, and embryo formation (Arisaka & Yui, 2019 ; Chu et al., 2019 ; Evans et al., 2019 ). Growth factors mainly include epidermal growth factor (EGF), platelet-derived growth factor (PDGF), fibroblast growth factor (FGF), and transforming growth factor beta (TGF-β) families (Goh et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we designed new polyrotaxane hydrogels to provide three‐dimensional microenvironments with suitable molecular mobility to regulate cellular responses. Considering that the molecular mobility of polyrotaxane surfaces acts as a key factor in dominating cellular responses, 11,21–23 we devised a method for fabricating hydrogels using only polyrotaxanes that can be cross‐linked at the terminals of the axis polymers. Although some researchers have already fabricated polyrotaxane hydrogels cross‐linked at the terminals, they used pseudo‐polyrotaxanes 24 .…”
Section: Introductionmentioning
confidence: 99%